ACT-07 Clinical Trials of 11C-Methionine PET for brain tumors. (28th November 2020) - Yamaguchi, Shigeru; Shiga, Tohru; Hirata, Kenji; Terasaka, Shunsuke; Kobayashi, Hiroyuki; Shimosegawa, Eku; Kagawa, Naoya; Hirayama, Ryuichi; Kinoshita, Manabu; Kijima, Haruhiko; Fujii, Masazumi; Ichikawa, Masahiro; et al.
Abstract: Background: Although 11C-Methionine (MET) PET has widely used, 11C-MET tracer has not been approved in Japan. We conducted multi-center prospective clinical trials using MET for drug approval in diagnosis of brain tumors[Methods] Two trials using 11C-MET PET were performed in Hokkaido University, Osaka University and Fukushima Medical University; 1) Diagnostic accuracy in differentiating tumor recurrence from radiation injury after radiotherapy in brain tumors, 2) The diagnostic efficacy in newly-diagnosed gliomas. 1) The patients with suspected brain tumor recurrence underwent MET and 18F-Fluorodeoxyglucose (FDG) PET. When the target lesion showed MET and/or FDG uptake, the patients underwent target resection for pathological confirmation. Positive prediction values of each tracer uptake were assessed as primary outcome measure, and the sensitivities and specificities of each PET exams were also assessed. 2) The patients with suspected gliomas underwent MET PET. Tissue samplings were performed from MET uptake lesions without contrast-enhancement on MRI in each patient, and evaluated the existence of tumor cells. Diagnostic additional values of MET PET on contrast-enhanced MRI was also investigated. Safety of MET PET was also assessed in each trial.[Result] 1) 57 cases were investigated. 38 cases underwent surgery and 32 cases (84%) were confirmed tumor recurrence histopathologically. MET and FDG uptake in 32 recurrence cases were 100% and 50%, respectively. Sensitivities and specificities of tumor recurrence were 84% and 89% in MET, and 100% and 56% in FDG. 2) 53 glioma cases were enrolled. Viable tumor cells were proven in 98% in MET uptake lesion without contrast-enhancement. In 42 out of 53 cases (78%), MET PET depicted tumor area beyond the contrast-enhancement area on MRI. No severe adverse events were observed in both trials. [Conclusions] MET PET were effective in diagnosis of brain tumors, and safety of MET was demonstrated.